1985
DOI: 10.1097/00006842-198503000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Naloxone Reduces Food Intake in Humans

Abstract: Hypotheses generated from animal studies that the endogenous opioid system is an important modulator of food intake suggest that blockade of the system in humans should affect eating behavior. To assess this hypothesis, seven normal volunteers were given 2 mg/kg naloxone or placebo on separate days in a double-blind, random but balanced cross-over experimental design. Compared to placebo, naloxone was found to reduce significantly total food intake from preselected prepared trays served 2.75 and 7.75 hours aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 19 publications
(15 reference statements)
2
23
0
Order By: Relevance
“…Similar inconsistent results have been observed in humans. Consistent reductions in food consumption after acute treatment of humans with the opioid receptor antagonists naloxone, naltrexone, or nalmefene have been reported (2,7,40,43,45,46). Subjective ratings of reward-related aspects of food palatability appear to be most related to the inhibitory effects of opioid antagonists on appetite in humans (46).…”
Section: Discussionmentioning
confidence: 74%
“…Similar inconsistent results have been observed in humans. Consistent reductions in food consumption after acute treatment of humans with the opioid receptor antagonists naloxone, naltrexone, or nalmefene have been reported (2,7,40,43,45,46). Subjective ratings of reward-related aspects of food palatability appear to be most related to the inhibitory effects of opioid antagonists on appetite in humans (46).…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, all but one human study (Hetherington et al, 1991) employing opioid receptor antagonists, including naloxone (Thompson et al, 1982;Trenchard and Silverstone, 1983;Cohen et al, 1985;Drewnowski et al, 1992;MacIntosh et al, 2001), naltrexone (Fantino et al, 1986;Jonas and Gold, 1986;Melchior et al, 1989;Bertino et al, 1991;Chatoor et al, 1994;Gray, 1996, 1997), and nalmefene (Yeomans et al, 1990;Yeomans and Wright, 1991), found significant decreases in caloric intake (Yeomans and Gray, 2002).…”
Section: Opioid Antagonists May Improve Hedonic Deficits In Patients mentioning
confidence: 99%
“…A possible connection between eating disorders and endoge nous opioids has been proposed in various animal studies [ 1 ] and has been both confirmed [2][3][4][5], and doubted [6,7] in studies of humans. At present, endogenous opioid activity in bulimia is still unclear.…”
Section: Introductionmentioning
confidence: 99%